Professor Philip J. Rosenfeld: OCT angiography and its application in macular diseases - Seliman, Helen; Xu, Elaine (Annals of Eye Science; Vol 2 (July 2017): Annals of Eye Science, 2017)
Dr. Philip J. Rosenfeld (Figure 1) received both his MD and PhD degrees from the Johns Hopkins School of Medicine, and he completed a research fellowship and residency in Ophthalmology at the Massachusetts Eye and Ear Infirmary, Harvard Medical School. Following his residency, Dr. Rosenfeld completed a Vitreoretinal fellowship at the Bascom Palmer Eye Institute, University of Miami Miller School of Medicine. In 1996, he joined the faculty of the Bascom Palmer Eye Institute where he is now an associate professor of Ophthalmology. Dr. Rosenfeld is a member of the American Academy of Ophthalmology (AAO), the American Society of Retinal Specialists (ASRS), the Retina Society, the Macula Society, and the Association for Research in Vision and Ophthalmology (ARVO).